The Role of Teachers in Implementing Sex Education Through Learning "Puberty Phase" Semester 2 Class V SD N 1 Wonokampir - Wardani, Sahar; Sunarko, Asep; Nasokah, Nasokah (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This study aims to describe the role of teachers in implementing sexual education through puberty learning in class V of SD N 1 Wonokampir in the 2024/2025 Academic Year. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The subjects in this study consisted of homeroom teachers of class VI as implementers of puberty learning, class V students as recipients of the material, and the principal as a policy maker and supporter of the implementation of sex education in schools. The results of the study show that teachers have a significant role in delivering sexual education material with an approach that is appropriate to the development of the students' age. The strategies used include a personal approach, utilization of technology media, and collaboration with external parties. Students showed a good understanding of puberty material and felt more prepared to face the physical and emotional changes they experienced. This study concludes that sexual education provided from an early age is very important to form a sense of responsibility, maintain health, and prevent inappropriate actions. This education is also a preventive measure against the negative influence of inappropriate information that can be accessed by children outside of school.